Sistem Aplikasi Manajemen PAUD Kb Tsamrotul Hikmah - Rahmawati Rahmawati; Muhdiatul Zannah; Wasis Haryono (Jurnal Kendali Teknik dan Sains, 2025)
Advances in information technology have had a major impact on the education sector, including at the Early Childhood Education (PAUD) level. To improve the quality of education services, PAUD institutions are required to implement a more sophisticated, accurate, and efficient management system through the use of an integrated information system. This study raises various obstacles faced by PAUD KB Tsamrotul Hikmah, especially in terms of recording teacher attendance, submitting leave, and managing finances that still use manual methods. This conventional system has been shown to reduce work effectiveness, increase the possibility of errors, and weaken the transparency and accountability aspects of the institution. To overcome these problems, an information system was developed to support automated administration processes and more systematic data management. The findings of this study indicate that digitalization of administration can improve work efficiency and data accuracy, as well as build public trust in the institution. Therefore, the implementation of an integrated information system is considered a strategic step in creating more professional, open, and sustainable PAUD management.